Video analysis of concussion mechanisms and immediate management in French men`s professional football (soccer) from 2015 to 2019 - Cassoudesalle, H.; Laborde,B.; Orhant, E.; Dehail, P. (Scandinavian Journal of Medicine & Science in Sports, 2021)
In this study, the concussion mechanisms were analyzed in male professional competition football, with the main objective to specify the frequency of head-to-head impact, and immediate management of the concussed players was described in order to check its compliance with the recommendations of football`s governing bodies. Based on continuously recorded data from the French Football Federation (FFF), a retrospective database of all reported concussions during matches in the 1st and 2nd French Male leagues was generated comprising seasons 2015/16-2018/19. Injury mechanisms, playing action, immediate medical assessment and management of concussed players, and foul play—referee`s decision, were analyzed from video recordings. In total, 41 concussions were reported (incidence rate of 0.44/1000 hours of match exposure [95% CI: 0.40 to 0.49]) of which 36 were identified and analyzed on video sequences. The commonest playing action leading to concussion was aerial challenge (61%), and the main mechanism was head-to-head impact (47%). Following the head impact, 28% of concussed players were not medically assessed on pitch and 53% returned to play the same match. Head-to-head impact was not associated with systematic medical assessment, nor with foul play. In conclusion, the main cause of concussions involved head-to-head impact occurring when two players challenge for heading the ball in the air. The detection of potential concussive head impacts and the immediate management of players possibly concussed during matches remain insufficient according to the international recommendations. Some rules changes, with particular vigilance in case of head-to-head impact, should be discussed.